MAIN STAGES OF FORMATION AND DEVELOPMENT ETHNO-INSTRUMENOLOGY IN KAZAKHSTAN (ON THE PROBLEM OF STUDYING FOLK MUSIC IN RK) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the main stages of the formation and development of ethnoinstrumental studies in Kazakhstan.
Keywords: musicologist-folklorist, Kazakh folk instruments.